187k views
4 votes
Let f(x) = 3x^2+5, g(x)=3x-4. Find the following value or expression
(F*g)(x)=

User GLP
by
6.0k points

1 Answer

12 votes

Answer:

(f οg )(x) = 27 x² -36 x + 53

Explanation:

Explanation:-

Given the function f(x) = 3 x² +5 and g(x) = 3x-4

(f οg )(x) = f(g(x)

= f(3x-4)

= 3 ( 3x-4)² +5 ( ∵ f(x) = 3 x² +5)

= 3 ( 9 x² - 2(3x)(4)+(4)²) +5

= 3 ( 9 x² -12 x + 16) +5

= 27 x² -36 x + 48 +5

= 27 x² -36 x + 53

Final answer:-

(f οg )(x) = 27 x² -36 x + 53

User Zindel
by
5.9k points